2020
DOI: 10.1177/1947603520976767
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis and Cell Viability of Nine Amnion, Chorion, Umbilical Cord, and Amniotic Fluid–Derived Products

Abstract: Objective Amnion products are used in various musculoskeletal surgeries and as injections for joint pain with conflicting reports of cell viability and protein contents. The objective of this study was to determine the full proteome and examine cell viability in 9 commercial amnion products using an unbiased bottom-up shotgun proteomics approach and confocal microscopy. Design Products were subjected to liquid chromatography–tandem mass spectrometry (LC-MS/MS) analysis and searched against a UniProt Homo sapie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…We found cell viability is poorly preserved in cryopreserved CAM, which is consistent with many previous studies with different measurement methods [16,17,33,41,42]. A comparison study of cell viability of cryopreserved human AM using a luminescence cell viability assay by Wagner and others (2018) revealed an intense decrease of metabolic cell activity of preserved AM in −80 • C. Luminescence signals of tissue preserved in glycerol at 14 days and 30 days were 67.90 and 49.12, respectively, which were significantly reduced compared to 238.56 of fresh AM [17].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found cell viability is poorly preserved in cryopreserved CAM, which is consistent with many previous studies with different measurement methods [16,17,33,41,42]. A comparison study of cell viability of cryopreserved human AM using a luminescence cell viability assay by Wagner and others (2018) revealed an intense decrease of metabolic cell activity of preserved AM in −80 • C. Luminescence signals of tissue preserved in glycerol at 14 days and 30 days were 67.90 and 49.12, respectively, which were significantly reduced compared to 238.56 of fresh AM [17].…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, evaluations of cell viability of fresh and cryopreserved human AM by trypan blue and EZ4U cell proliferation and cytotoxicity assay [16] and MTT assay imaged with confocal microscopy [41] showed that cryopreserved AM had marked reduction of cell viability. Moreover, no live cells were identified in any AM commercial products preserved by freeze-dried method, dehydration, or cryopreservation [42]. Dramatic reduction of cell viability demonstrated in our result as well as studies of human AM, implies that cryopreserved AM are not suitable for regenerative medicine purposes.…”
Section: Discussionmentioning
confidence: 55%
“…The presence of collagen VI may play an important role in promoting chondrocyte proliferation ( 29 ). Other proteins found in AM such as collagen XII are known to interact with collagen VI, resulting in up-regulation of tissue regeneration ( 30 ). The presence of keratin could also be beneficial as studies have shown its role in increasing cellular adhesion and inducing polarization of inflammatory M1 macrophages to antiinflammatory M2 phenotype ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…cells 43. Likewise, despite the apparent presence of regulatory proteins in amniotic products, such as IL-1Ra and TIMP-2, further laboratorial analysis could not confirm these results.…”
mentioning
confidence: 81%
“…Likewise, despite the apparent presence of regulatory proteins in amniotic products, such as IL-1Ra and TIMP-2, further laboratorial analysis could not confirm these results. Therefore, the perception that amnion tissues provide live cells and modulatory molecules to assist tissue regeneration could not be supported 43. Caution should be taken since cell viability in the cord blood product is usually less than the values reported by commercial entities.…”
mentioning
confidence: 99%